EP807 The risk of malignancy of unilocular ovarian cysts: a systematic review and meta-analysis. (1st November 2019) - Buggio, L; Dridi, D; Frattaruolo, MP; Reschini, M; Di Loreto, E; Chiaffarino, F; Parazzini, F; Vercellini, P
Abstract : Introduction/Background: Unilocular adnexal cysts are a common condition. The oncogenic potential of unilocular adenexal masses has often led to an overtreatment with high health care costs and psychological distress. We conducted a systematic review and meta-analysis to estimate the rate of malignancy in adnexal lesions described as echoic and anechoic unilocular cysts at pre-operative transvaginal ultrasound examination. Methodology: We performed a Pubmed/MEDLINE search of papers published between January 1990–April 2019, using the terms 'unilocular ovarian cysts' or 'simple ovarian cysts' combined with 'ovarian cancer' or 'surgery' or 'histology' or 'transvaginal ultrasound'. Only studies published as full-length in English and reporting original data were included. The present review and meta-analysis were performed according to the PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analyses) and MOOSE guidelines. Results: From 35 selected studies, we extracted data on ovarian malignancy in the total series, and separately for premenopausal and postmenopausal women. Flowchart of the study selection process is shown in figure 1 . Of the 2229 surgically removed lesions classified as unilocular cysts at pre-operative transvaginal ultrasound, 24 (1.1%; 95% CI: 0.73–1.60) were malignant (among these 12 had borderline malignancy: 0.5%). The rates were lower for premenopausal women (6/1034, 0.6%;95% CI: 0.27–1.26) than postmenopausal ones (12/377, 3.2%; 95% CI: 1.83–5.48). Of the 2296 surgically removed lesions classified as anechoic unilocular ovarian cysts on ultrasound, 20 (0.9%; 95% CI: 0.56–1.34) were malignant (among these 8 had borderline malignancy: 0.3%). The rates were lower for premenopausal women (3/907, 0.3%; 95% CI: 0.11–0.97) than postmenopausal ones (13/681, 1.9%; 95% CI: 1.56–3.96). Conclusion: The malignancy rate in surgically removed unilocular adnexal cysts is low. The choice between surgery and expectant management should be individualized, and personalized counseling with the patient is advised to avoid the risk of overtreatment. Disclosure: Nothing to disclose.